2019
DOI: 10.11604/pamj.2019.34.29.11283
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological features of knee osteoarthritis in patients attending the university hospital of Kinshasa, Democratic Republic of Congo

Abstract: IntroductionThe aim of the present study was to describe the clinical and radiological features of knee osteoarthritis in Congolese outpatients attending the University Hospital of Kinshasa (UHK).MethodsA cross-sectional study was performed in the rheumatology unit of the UHK from January to August 2012. Patients were consecutively recruited. The diagnosis of Osteoarthritis (OA) was based on the criteria of the American College for Rheumatology. Demographic, clinical and x-rays data were collected. The X-rays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 26 publications
0
15
2
1
Order By: Relevance
“…Within this symptomatic/radiographic knee OA population, 94% had grade ≥2 OA and more than 70% had severe, grade 3/4, OA. 25 Asokan et al reported a 33.9% prevalence of symptomatic/radiographic knee OA among a population of female patients ≥40 years of age with mixed etiology OA in Bahrain. 17 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this symptomatic/radiographic knee OA population, 94% had grade ≥2 OA and more than 70% had severe, grade 3/4, OA. 25 Asokan et al reported a 33.9% prevalence of symptomatic/radiographic knee OA among a population of female patients ≥40 years of age with mixed etiology OA in Bahrain. 17 …”
Section: Resultsmentioning
confidence: 99%
“… 25 Asokan et al reported a 33.9% prevalence of symptomatic/radiographic knee OA among a population of female patients ≥40 years of age with mixed etiology OA in Bahrain. 17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O aumento do envelhecimento associado a crescente prevalência de obesidade, espera-se que as pessoas que sofram com a osteoartrose de joelho se eleve nos próximos anos. (LUKUSA et al, 2019).…”
Section: Propriedades Psicométricasunclassified
“…OA leads to the breakdown and gradual loss of joint cartilage, triggering debilitating pain and subsequent disability ( 3 ). The disease mainly affects the aging population, and >37% of individuals aged 60 years or older are affected by OA ( 4 ). At present, arthroscopic surgery and painkiller therapy are the main treatment options for OA; however, these treatment strategies result in 36,000,000 ambulatory care visits and 750,000 hospitalizations annually ( 5 , 6 ), leading to a high socioeconomic burden ( 7 ).…”
Section: Introductionmentioning
confidence: 99%